PERANCANGAN SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT PADA PABRIK KERUPUK(Studi Kasus : CV Bintang Harapan Jawa) - Rania Ramadhina (2022)
The rapid dissemination of information is balanced with the development of current technology, causing a company not only to focus on sales, but also to focus on customers for facing the business competition. The services provided by CV Bintang Harapan Jaya for its customers are still not optimal enough. The Submission of complaints given by customers is still using word of mouth, so it is often not known by the branch or factory. Therefore, we need an information system using a Customer Relationship Management approach that can provide satisfactory information and services for customers with the aim of increasing customer loyalty. The system design using the Waterfall method and visual modeling with the Unified Modeling Language (UML). The results are, the form of an information system that can make it easier for customers to find information and provide services to submit their complaints to CV Bintang Harapan Jaya so that the process becomes more effective and efficient.